The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2318-0331.0217170054
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationarity in maximum annual daily streamflow series from Southern Brazil

Abstract: Extreme streamflow values estimates are important for flood risk assessment and also for the design and operation of hydraulic structures. The behavior of this hydrological variable is under climate and land use changes effects and river's course modifications caused by construction and operation of large reservoirs. The assumption of stationarity commonly adopted in flood frequency and magnitude analysis studies is questionable under such circumstances. In this work we identified nonstationary annual maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
3
0
2
Order By: Relevance
“…Future studies could involve evaluating model uncertainties (BLAZKOVA;BEVEN, 2002;ZENG et al, 2016), as well as the shape and distribution of design hyetographs (e.g., Grimaldi et al, 2012). We also did not consider a possible nonstationarity of discharges existent in the Itajaí-Açu basin, although some studies have suggested its existence in Southern Brazil (e.g., Bartiko et al (2017)), and this suggests further developments for this topic.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies could involve evaluating model uncertainties (BLAZKOVA;BEVEN, 2002;ZENG et al, 2016), as well as the shape and distribution of design hyetographs (e.g., Grimaldi et al, 2012). We also did not consider a possible nonstationarity of discharges existent in the Itajaí-Açu basin, although some studies have suggested its existence in Southern Brazil (e.g., Bartiko et al (2017)), and this suggests further developments for this topic.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bartiko et al (2017) also found clusters of increasing annual maximum daily flow in the Upper Uruguay basin. However, since large water flows in SB are linked to recurrent climatic features such as the ENSO phenomena (Krepper et al, 2003;Maciel et al, 2013;Pasquini & Depetris, 2007;Robertson & Mechoso, 1998;Silva et al, 2017), the nonstationarity in the flood time series might be related to oscillatory components rather than to a linear trend.…”
Section: Water Resources Researchmentioning
confidence: 87%
“…In Southern Brazil (SB) there were increases in annual average, minimum, and maximum streamflow (Bartiko et al, 2017;Berbery & Barros, 2002;Detzel et al, 2016;Doyle & Barros, 2011;Hirata et al, 2010;Marques, 2012;Pasquini & Depetris, 2007), generally associated with rainfall variability (Doyle & Barros, 2011;Maciel et al, 2013;Saurral et al, 2008). The Uruguay and the Paraná rivers, which downstream become the La Plata River, have experienced in the last century one of the greatest annual streamflow increases in the world (Milliman et al, 2008;Piao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Devido à possibilidade de ocorrerem alterações nas estatísticas das séries hidrológicas ao longo do tempo, diversos estudos buscaram avaliar a estacionariedade de séries históricas em bacias hidrográficas de diferentes regiões do mundo (Marengo, 2004;Yeste et al, 2018;Wilcox et al, 2018;Sun et al, 2018;Harrigan et al, 2018;Gu et al, 2019;Forootan, 2019;Mirdashtvan et al, 2020;Stephens e Bledsoe, 2020). No Brasil, detecta-se viés tanto de incremento quanto de decréscimo da vazão em diversas bacias e, em boa parte dos estudos, notam-se mudanças significativas após a década de 70 (Genta et al, 1998;Müller et al, 1998;Bartiko et al, 2017;Tozzi e Fill, 2020). Tendências de aumento das vazões são relatadas por Genta et al (1998), Müller et al (1998), Gueter e Prates (2002), Sáfadi (2004), Rosin et al (2015), e Teixeira et al (2020).…”
Section: Introductionunclassified
“…Viés decrescente é relatado por Moraes et al (1998), Marengo e Alves (2005) e Melo et al (2019). No Sul do Brasil, as afluências mostraram-se não-estacionárias nos estudos de Detzel et al (2011) e Bartiko et al (2017). Com relação às séries de precipitação no Brasil, relatase tanto viés crescente (Berlato e Cordeiro;Nunes et al, 2018;Quadros et al, 2018;Guedes et al, 2019) como decrescente (Santos e Nishiyama, 2016), e ainda ausência de tendência (Sá et al, 2018;Alcântara et al, 2019;Melo et al, 2019).…”
Section: Introductionunclassified